THE CORA INDIANS OF BAJA CALIFORNIA: THE RELACION OF FATHER IGNACIO MARIA NAPOLI, S.J.; SEPTEMBER 20, 1721 - Moriarty, James Robert (autor) (BAJA CALIFORNIA TRAVELS SERIES, 19, 1970)
INCLUYE BIBLIOGRAFIA